(untitled) (Research, Society and Development, 2022)
Every individual has the right to accept or refuse preventive, diagnostic or therapeutic proposals that have the potential to affect their physical-psychic or social capacity. Objective: The present work aims to analyze the perspectives of medical students from a public university on the exercise of patients’ autonomy during health care. Methodology: The study is qualitative, descriptive and transversal, using the Collective Subject Discourse. 58 medical students participated in the research, most of them belonging to the 3rd period. Results: Regarding the knowledge of autonomy as a principle of bioethics, most claimed to have knowledge, as well as which document ensures the patient’s autonomy, stating that it is the Free and Informed Consent Term, almost all knew its mandatory in interventional procedures. In cases of diagnosis of serious diseases, most prefer that it is informed to the patient. Regarding academic training in bioethics, everyone understood it as essential. Conclusion: Bioethics, as a discipline that encourages humanization and a good doctor-patient relationship, promotes professional training and provides future doctors with legal support to practice their profession, was unanimously considered essential in medical graduation. Autonomy, as a principle of bioethics, portrays, from the student’s perspective, the ability to make decisions, freedom, consolidating a right of the doctor and the patient.